Efficacy of chloroquine, chloroquine plus sulphadoxine-pyrimethamine, and amodiaquine for treatment of vivax malaria in Bangka island, Indonesia: a randomized trial (Medical Journal of Indonesia, 2008)
Plasmodium vivax malaria resistant to chloroquine is alarming in Indonesia and has been also reported in other countries. An alternative drug is needed. The study was a prospective evaluation and a comparative study of the therapeutic efficacy of chloroquine 25 mg base/kg bw for 3 days (CQ3, n=75), CQ3 plus sulfadoxine-pyrimethamine based on pyrimethamine dosage of 1.25 mg/kg bw single dose (SP1) [CQ3+SP1, n=84] and amodiaquine 25 mg base/kg bw for 3 days (AQ3, n=83) in symptomatic vivax malaria patients in children and adults. The new version of 2001 WHO test system was used in this study. PCR for genotyping was also done to validate and confirm the treatment outcomes. The therapeutic efficacy of CQ3, CQ3+SP1 and AQ3 on day 14 were very high (94.4%, 97.4% and 98.8%), and dropped on day 28 (81.7%, 87.2% and 96.2% by evaluable analysis; 78.9%. 82.0% and 92.5% after confirmation with PCR; and 74.7%, 78.0% and 90.2% by intention to treat analysis). Most of the ACPR cases (>96%) showed hematological recovery. Gametocyte carriages were documented on day 7 (2.9%, 1.3% and 1.2%), day 14 (4.3%, 1.3% and 1.2%) and day 28 (6.6%, 4.2% and none) in CQ3, CQ3+SP1 and AQ3 groups. Of these 3 regimens, AQ3 showed a better therapeutic efficacy than CQ3 and combined CQ3+SP1 by day 28. Introducing primaquine at the beginning of treatment day or giving a radical treatment in vivax malaria may improve the cure rate. (Med J Indones 2008; 17: 96-106)